HIV/AIDS Prevention, Faith, and Spirituality among Black/African American and Latino Communities in the United States: Strengthening Scientific Faith-Based Efforts to Shift the Course of the Epidemic and Reduce HIV-Related Health Disparities - Sutton, Madeline Y. (Journal of religion and health, 2013)
Black/African American and Latino communities are disproportionately affected by the domestic HIV/AIDS epidemic. Blacks/African Americans and Latinos are also more likely to report a formal, religious, or faith affiliation when compared with non-Hispanic whites. As such, faith leaders and their institutions have been identified in the National HIV/AIDS Strategy as having a vital role to serve in reducing: (1) HIV-related health disparities and (2) the number of new HIV infections by promoting non-judgmental support for persons living with and at risk for HIV/AIDS and by serving as trusted information resources for their congregants and communities. We describe faith doctrines and faith-science partnerships that are increasing in support of faith-based HIV prevention and service delivery activities and discuss the vital role of these faith-based efforts in highly affected black/African American and Latino communities.